INTERAKSIONAL SIMBOLIK AKTOR GOVERNANCE DALAM KEBIJAKAN PERTAMBANGAN DI HUTAN LINDUNG GUNUNG TUMPANG PITU BANYUWANGI - Muhamad Imron (Universitas Merdeka Malang, 2016)
Abstract Although it often is imaginary, in fact, still quite well-being can be packaged attractively in the extractive industry practices. Welfare as a result of mining operations is actually the result of though construction on the existing realities. Welfare often positioned or constructed as a symbol that can facilitate acceptance of a policy. Communication patterns constructed by political elites through welfare bids can shut other desires that may be veiled. Interaction between actors presented governance (State-Private Sector-Civil Society-MNC) on mining operations in the Mountain Protection Forest Mixed Pitu Banyuwangi shows us a form of political communication and propaganda loaded. Color and pattern mining policy is dominated by the preferences and communication ansih elite level. Sound Governance approach is expected to provide opportunities for the emergence of parallel patterns of interaction for all potential possessed by all actors. All actors must be able to stand on equal footing in the face of all the problems that inevitably arise in every operation of the mining industry, such as environmental damage to the ecosystem, social and cultural impact, until the achievement of the welfare of the local community. Welfare should ideally not be imaginary side of an extractive industry, it should be presented through the strategic role of all actors existing governance. The approach used in this study is qualitative wrapped with critical paradigm. This is done to strip to the deepest problems of the cases in the study. While policy analysis is done by using the approach of Walt and Gilson through the blades of analysis for the study of policy such as policy analysis model consisting of aspects of the content, context, process, and actor. While Palmer Short presents a number of relevant questions in a critical review of a policy. In this study, both approaches are combined and then reviewed again by the advocacy coalition framework as a form of triangulation methods of analysis. This study aims to reveal the form of political communication as well as see the symbolic interaksionalisme actor governance in the mining policy practices.DOI : https://doi.org/10.26905/nomosleca.v2i2.618